The President’s Power and Anti-Corruption Policy: What Can Be Learned from New Order Experience - Oce Madril (Faculty of Law, Hasanuddin University, 2017)
The New Order government led by President Soeharto was supposed to be a regime that would ameliorate the abuse of power conducted by the previous government. One of the important agendas for the New Order government was overcoming the issues regarding the abuse of authority and corruption in the government sector. Several legislations, Presidential legal policies and institutions were formed to carry out such mission. However, the New Order government eventually failed and became a corrupt regime. This study concludes that notwithstanding Indonesia theoretically had an institutional framework to combat corruption under the New Order government, it failed to eradicate corruption. The failure of anti-corruption policies under the New Order era was caused by 3 forms of failure. Firstly, the failure to build a democratic and anti-corruption presidential power. Secondly, the failure to build a comprehensive anti-corruption policy. Thirdly, the failure to build an effective anti-corruption agency. The method employed in this study is a combination of several approaches between the statutory approach, historical approach and conceptual approach. The main data used in this study is the literature which are consists of previous research, legislation and Presidential policies.